2009
DOI: 10.1089/ham.2008.1028
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning with Cobalt Attenuates Hypobaric Hypoxia-Induced Oxidative Damage in Rat Lungs

Abstract: Shukla, Dhananjay, Saurabh Saxena, Purushotman Jayamurthy, Mustoori Sairam, Mrinalini, Singh, Swatantra Kumar Jain, Anju Bansal, and Govindaswamy Ilavazaghan. High Alt. Med. Biol. 10:57-69, 2009.-Hypoxic preco759nditioning (HPC) provides robust protection against injury from subsequent prolonged hypobaric hypoxia, which is a characteristic of high altitude and is known to induce oxidative injury in lung by increasing the generation of reactive oxygen species (ROS) and decreasing the effectiveness of the antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 55 publications
4
26
0
Order By: Relevance
“…Surprisingly, when combined with irradiation at low or moderate doses, CoCl 2 could reduce the levels of ROS generated by IR, which was confirmed by an increase in cell viability. Toxicological experiments have shown that CoCl 2 protects cells against chemical insults and blocks injury to biological systems, and that induction of the expression of HIF-1α plays an important role in this effect [30, 31]. Similarly, our results show that like hypoxia, CoCl 2 increases levels of HIF-1α and enhances cellular radio-resistance.…”
Section: Discussionsupporting
confidence: 75%
“…Surprisingly, when combined with irradiation at low or moderate doses, CoCl 2 could reduce the levels of ROS generated by IR, which was confirmed by an increase in cell viability. Toxicological experiments have shown that CoCl 2 protects cells against chemical insults and blocks injury to biological systems, and that induction of the expression of HIF-1α plays an important role in this effect [30, 31]. Similarly, our results show that like hypoxia, CoCl 2 increases levels of HIF-1α and enhances cellular radio-resistance.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to the protective effect in cell culture, in vivo studies were also performed. We exposed rats to a simulated altitude of 8,000 m for 48 h for the following reasons: (1) smaller animals have higher capillary density in tissue, which makes them more resistant to hypoxia than humans [32] , and (2) most high-altitude-induced problems, such as high-altitude pulmonary edema, generally develop within 2-4 days after arriving at high altitude [33] . Our observation of an increase in lung water content following exposure to hypobaric hypoxia coincided with the reports of earlier investigators [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…There are also contrasting findings showing the beneficial roles of Co. Shukla et al [145] revealed that hypoxic preconditioning with Co diminishes hypobaric hypoxia-induced oxidative damage in rat lungs. Co(II) b-ketoaminato complexes exhibited a prospective pharmacological benefit as novel inhibitors of neuroinflammatory processes [146].…”
Section: Chromiummentioning
confidence: 99%